Promoting vascular healing using nanofibrous ticagrelor-eluting stents - Lee, Cheng-Hung (Int J Nanomedicine, 2018)
OBJECTIVE: The current treatment of atherosclerotic coronary heart disease with limus-eluting stents can lead to incomplete endothelialization and substantial impairment of arterial healing relative to treatment with bare-metal stents. The sustained and local delivery of ticagrelor, a reversibly binding P2Y12 receptor inhibitor, using hybrid biodegradable nanofibers/stents, was developed to reduce neointimal formation and endothelial dysfunction. METHODS: In this investigation, a solution of ticagrelor, poly(D,L)-lactide-co-glycolide, and hexafluoro isopropanol was electrospun to fabricate ticagrelor-eluting nanofibrous drug-eluting stents. The in vitro and in vivo ticagrelor concentrations were measured using a high-performance liquid chromatography assay. The effectiveness of ticagrelor-eluting stents was examined relative to that of sirolimus-eluting stents. RESULTS: Adequate ticagrelor levels were detected for four weeks in vitro. Less HES5-positive labeling was found near the ticagrelor-eluting stented vessels (0.33±0.12) than close to the sirolimus-eluting stented vessels (0.57±0.15) (p<0.05). Four weeks after deployment, the ticagrelor-eluting stent also exhibited an up-regulated local expression of SOD1 in the stenting area (p<0.001). The ticagrelor-eluting stent substantially preserved endothelial function and re-endothelialization, minimized inflammatory responses, and inhibited neointimal hyperplasia. CONCLUSION: Ticagrelor-eluting stents may provide an alternative route for treating patients at a high risk of bleeding to preserve endothelial recovery and to reduce smooth muscle proliferation.